Iodixanol Density Gradient Preparation in University of Wisconsin Solution for Porcine Islet Purification - Michael P.M. Van der Burg; John M. Graham (The Scientific World Journal)
Previously published as Graham, J.M. (2002) Purification of Islets of Langerhans from porcine pancreas. TheScientificWorldJOURNAL 2, 1657–1661. ISSN 1537-744X; DOI 10.1100/tsw.2002.847.Generally, prior to the purification of isolated pancreatic islets, the collagenase-digested tissue is incubated in the University of Wisconsin solution (UWS; ~320 mOsm) for osmotic stabilization to preserve or improve the density differences between islets and acinar fragments. The adverse effects arising from the subsequent pelleting and resuspension of the islets in a second, different (often highly hyperosmotic) purification solution are avoided in the protocol described here; preparation of the purification medium is simply achieved by mixing the UWS preincubated islets with a second UWS containing the inert impermeant iodixanol. Flotation of the islets isolated from juvenile porcine pancreases through this mildly hypertonic (~380 mOsm) gradient of iodixanol-UWS achieves a much higher recovery of islets of an improved viability than the customary method using a Ficoll gradient. The method has been extended to human islet purification.